2015
DOI: 10.1590/0102-311x00178313
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in the context of HIV and syphilis infection in a population of men who have sex with men (MSM) in Salvador, Bahia State, Brazil

Abstract: Social, individual, and programmatic vulnerability of men who have sex with men (MSM) in the context of the HIV epidemic and other sexually transmitted infections (STI) is a reality in many countries. The survey Behavior, Attitudes, Practices, and Prevalence of HIV and Syphilis in Men Who Have Sex with Men in 10 Brazilian Cities selected 383 MSM in the city of Salvador, Bahia State, Brazil, using the respondent driven sampling (RDS) technique. Individual vulnerability: early sexual initiation (51%), average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
1
23
0
23
Order By: Relevance
“…Although several epidemiological studies have indicated anal sex as a risk factor for acquisition and transmission of T. pallidum among men who have sex with men [25][26][27], low evidence is found among heterosexual couples [22]. Indeed, this is one of the first investigations to report an association of anal sex between men and women and syphilis infection.…”
Section: Discussionmentioning
confidence: 79%
“…Although several epidemiological studies have indicated anal sex as a risk factor for acquisition and transmission of T. pallidum among men who have sex with men [25][26][27], low evidence is found among heterosexual couples [22]. Indeed, this is one of the first investigations to report an association of anal sex between men and women and syphilis infection.…”
Section: Discussionmentioning
confidence: 79%
“…A study conducted in Salvador showed the prevalence of syphilis in MSM was much higher (14%) than the general population of men (1.3%). Consequently, prevention and direct interventions for MSM should be carried out, including social policies aimed at improving their living conditions, reducing stigma, and facilitating closer ties with health services 13 .…”
Section: No Yes No Yesmentioning
confidence: 99%
“…In the context of vulnerability, investigators consider some populations as more likely to acquire syphilis: individuals living in seclusion, homeless people, drug users, men who have sex with men (MSM), those co-infected with human immunodeficiency virus (HIV), and pregnant women [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…These actions only become effective if their needs are understood and met. [19][20][21][22][23] Therefore, comprehension only occurs if there is understanding of what is affecting health. Some diseases can be prevented simply, such as performing simple hygiene, properly, to prevent the growth of microorganisms.…”
Section: Discussionmentioning
confidence: 99%